Gestión turística del Gad municipal y su incidencia en el desarrollo socioeconómico del cantón caluma, año 2020. plan estratégico de promoción turística. - García Liscano, Roció Ernestina (2021)
In Ecuador, the National Government carries out a set of plans, programs and projects, called PLANDETUR 2020, in order to stimulate and strengthen tourism activity and consolidate it in the near future, as the first source of income in the country. The Caluma canton has many benefits, tourism products and services that have not yet been fully exploited, there is no greater impact on its economic and social development, the present research has as a general objective to establish the incidence of tourism management of the Municipal GAD In the socioeconomic development of the Canton Caluma, year 2020, the conceptual, theoretical and legal bases that base the variables of the subject were included. As a methodology, inductive-deductive methods were used as logical reasoning strategies in the production of knowledge, instruments such as the survey that served to identify necessary measurements in the development of the research, the questionnaire that was applied to 5 officials of the municipality to obtain information homogeneous, whose responses allowed knowing the reality of the tourism management developed by the institution and 374 inhabitants to assess the degree of socioeconomic development of the population, as well as the observation guide to establish the level of compliance with the budget proforma of programs and projects of the economic component. The research results were obtained from the instruments, based on this the conclusions and recommendations were raised, to finish a solution proposal was developed as a preventive measure against the problem.